Enhancing Student Learning Outcomes Using Game-Based Learning - Saputra, Febry; Dian Arief Pradana; St. Shabibatul Rohmah (LUNAR, 2025)
The study investigated the impact of game-based learning using Wordwall media in enhancing learning outcomes and student engagement among eighth-grade students in an English grammar lesson. This research was initiated to address low grammar mastery and engagement at the research location, where preliminary data showed an average pretest score of 67.4 with most students failing to meet the minimum passing criteria. This study used a quantitative pre-experimental design with a pretest-posttest one-group design, involving 20 students. Data were collected through pretest-posttest assessments and observations measuring behavioral, emotional, and cognitive engagement. Paired t-test results showed significant improvement in learning outcomes, with a mean score increase of 14.20 (SD = 5.58). The calculated t-value was 11.384, exceeding the critical t-table value of 2.093 at df = 19, and the two-sided significance value was 0.000, confirming statistical significance. Observations revealed increased engagement across all three dimensions. These findings demonstrate the efficacy of game-based learning in enhancing academic performance and student engagement, offering an effective solution to the learning challenges identified. Further research is recommended to explore long-term effects and applicability across different subjects and age groups.